Impact of Store Ambience on Impulse Purchasing of Apparel Consumers - Vishal Trivedi; Pradeep Joshi; K. N. Chatterjee; Girendra Pal Singh (Tekstilec, 2022)
The aim of this research was to identify the impact of store ambience on apparel consumer impulse purchase behaviour. In this paper, the influence of window display (WD), promotional offers (PO), store layout (SL), background music (BM) and fragrance of store (FOS) on consumer impulsive buying behaviour (IBB) for apparel was evaluated. The study was performed among 210 consumers in Delhi (NCR), at the DLF Mall of India, using a questionnaire developed based on existing literature. The research data was analysed using the factor analysis, and correlation and linear regression tests. According to the research findings, store features such as window display, promotional offers and fragrance have a significant effect on impulse purchase behaviour. The current study makes some suggestions for retailers to improve the ambience of their stores in order to boost impulse buying among apparel buyers.